Основные технологические процессы необходимые для изготовления мехатронных систем удовлетворяющие современные требования и проблемы их инструментального обеспечения на фоне призывов - "ИНДУСТРИЯ 4.0" - Турманидзе, Р. С.; Бачанадзе, В. И.; Попхадзе, Г. З. (НТУ "ХПИ", 2017)
In the presented work investigated the changes of power characteristics of deep drilling package of printed circuit board’s hard metal micro drills depending on the drilling depth, cutting data and geometry of the drill. In particular studied the nature of changes in axial efforts and torque depending on the drilling depth drill with different inclinations of the spiral grooves using specially designed highly sensitive devices, enabling direct measurement method. Based on the analysis of the results of the study, changes in the geometry of existing standard drills. Proposed new construction of micro drills vary-angle spiral grooves in such a way that the angle is the maximum value at the top of the drill and uniformly decreases towards the end of the working parts. The drills are manufactured with different inclinations of the spiral grooves. Based on the experiments of them chosen more for its near standing power rates to the standard drill bit and its comparative test with a standard drill bit, bringing them up to the breakage, thanks to which the proven advantages of drills new design. Taking into account the results of the experiments proposed drill elongated structures to improve performance by increasing the processing drilling depth and accordingly the number of plates in the package of printed circuit boards.
Keywords: работоспособность; микросверла; крутящий момент; режущий инструмент; твердосплавные микросверла; спиральные канавки; drilling; spiral drill; drill strength; drill wear